Comparison of efficacy and cost of different doses of steroids and immunoglobulin treatments for acute immune thrombocytopenic purpura - Akarsu, Saadet; Kiliç, Mehmet; Taşkin, Erdal; Kurt, Abdullah; Yilmaz, Erdal; Aygün, A. Denizmen (My University, 2005)
Immune thrombocytopenic purpura (ITP) is certainly a common and benign disease of infancy and childhood. The major complication is intracranial hemorrhage, the fear of which drives physicians to initiate treatment. The goals of therapy involve maintaining a safe platelet count while minimizing toxicities from the treatment. It has been reported that in severe cases, intravenous (IV) megadose methylprednisolone (IVMDMP) 500 mg/m 2/day for 5 days produces a more rapid response than conventional steroids. We want to compare the results of therapeutic efficacy and cost of IVMDMP, oral megadose methylprednisolone (OMDMP) (30 mg/kg/day, 3 days and 20 mg/kg/day, 4 days), and IV polyvalent immunoglobulin (IVIG) (1 g/kg/day, 2 days) for the treatment of acute ITP. Among 111 cases, aged between 1.5 months-16 years, diagnosed as acute ITP, 38 (34.3%) cases were treated with IVMDMP, 45 (40.5%) cases with OMDMP, and 28 (25.2%) cases with IVIG. At the end of 24 and 48 hours; 5, 7 and 14 days of therapy; and at 1 month of therapy, platelet counts were determined. Although the cost of IVIG is higher for the treatment of acute ITP, we did not observe any superior effect, and the effect of OMDMP was as efficient as IVIG and IVMDMP.
Akut immün trombositopenik purpura tedavisinde farkli dozlarda steroid ile intravenöz immünoglobülin tedavilerinin etkinlik ve fiyatlarinin karşilaştirilmasi
Keywords: Acute immune thrombocytopenic purpura; Childhood; Treatment